Students’ Conceptual Difficulties in Understanding Maps and Scales: An Exploratory Descriptive Study - Rahma Aulia Fithri; Najma Nur Mawaddah; Nurul Azmi; Mei Vita Romadon Ningrum (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to describe students' conceptual difficulties in understanding maps and scales in geography learning. The study uses a qualitative approach with an exploratory descriptive model. Data were collected through in-depth interviews, classroom learning observations, and analysis of student work documents. The Research subjects consisted of ten Year 10 students from Samarinda State Senior High School 8, who were purposively selected to represent variations in academic ability and learning characteristics. The study's results showed three main categories: difficulties understanding the concept of scale, difficulties converting distance units, and difficulties interpreting and reading maps. These difficulties were influenced by the weak connection between conceptual understanding, spatial representation, and students' real experiences. The findings emphasise the need for visual-based contextual learning supported by interactive digital media. Implicitly, this study provides a basis for teachers and curriculum developers to sustainably strengthen students' spatial literacy and geospatial thinking skills. These results are relevant for further Research examining the relationship between conceptual difficulties and innovative learning strategies in the secondary school context.